Evaluation of nonwoven geotextile drainage performance and experimental simulation of key processes in Yellow River sediment-backfilled reclaimed coal-mined subsided lands - Sun, Huang; Hu, Zhenqi; Song, Deyun; Wang, Shuai; Yu, Yi (International Journal of Agricultural and Biological Engineering, 2024)
The innovative utilization of Yellow River sediment to reclaim coal-mined subsided lands addresses dual environmental challenges by offering a sustainable remediation technique. However, efficient water drainage constitutes a significant hurdle in this context. The strategic placement of nonwoven geotextile at the tail end of the fill sections has ameliorated fine sediment loss and drainage efficacy issues. This study assesses various nonwoven geotextile grades for their effectiveness in moisture expulsion, integrating comprehensive evaluations and simulation tests of pivotal processes. The findings reveal that selected nonwoven geotextiles (N1, N2, T1, T2, T3, T4) demonstrate appropriate apparent opening size (AOS) and permeability, coupled with clogging resistance, aligning with theoretical criteria for soil conservation, water permeation, and blockage prevention. Crucial to the nonwoven geotextile’s clogging are factors such as apparent opening size (AOS), thickness, permeability, load capacity, gradient ratio (GR), and sediment retention - all requiring meticulous selection for real-world application. The choice of nonwoven geotextile in the drainage of Yellow River sediment reclaimed lands must hinge on a holistic assessment framework, encompassing retention, permeability, anti-clogging attributes, and additional performance metrics, to ensure that the materials fulfill the specific technical standards while remaining cost-effective. This study provides valuable insights into the selection and application of geotextiles in Yellow River sediment-backfilled reclamation drainage projects, contributing to the advancement of mine ecological restoration practices, particularly in the context of Yellow River sediment-backfilled reclamation projects. Keywords: nonwoven geotextile, drainage performance, Yellow River sediment, coal-mined subsided land, filling reclamation, engineering constructionDOI: 10.25165/j.ijabe.20241706.8897Citation: Sun H, Hu Z Q, Song D Y, Wang S, Yu Y. Evaluation of nonwoven geotextile drainage performance andexperimental simulation of key processes in Yellow River sediment-backfilled reclaimed coal-mined subsided lands. Int J Agric& Biol Eng, 2024; 17(6): 193–201.